CTDI versus New AAPM Metrics to assess Doses in CT: a case study - Maria Carolina Santana Campelo; Marcia Carvalho Silva; Ricardo Andrade Terini (Brazilian Journal of Radiation Sciences)
In modern CT, CTDI100 measurements would underestimate accumulated dose at the gantry center. AAPM TG 111 report proposed improved metrics for CT dosimetry, mainly for helical and wide beam width scanning. In this study, a methodology to assess CT dose, inspired on TG 111, was applied. Dosimeters were firstly calibrated in lab in beams like those utilized clinically. Using a reference 0.6cc Farmer chamber, two CT “pencil” chambers were calibrated in PKL by substitution method. Results showed differences ≤ 2% in the calibration coefficients, for three collimation apertures. A small 0.6cc chamber was calibrated in air kerma with this setup, without any collimator. After this, in a private Brazilian hospital, the small chamber was applied in dosimetry tests of a CT scanner, according to TG 111, determining Dose profiles and Equilibrium dose free-in-air (Deq,air) for some protocols and pitch values. Results showed that Deq,air increased when reducing pitch and Equilibrium dose-pitch product free-in-air (p.Deq,air) remain constant. In measurements with a 450mm CT phantom, differences between Planar Average Equilibrium Dose (Deq,p) and CTDIvol ranged between 30-37%. This occurs because CTDIvol cannot include dose profile "tail" contribution, caused by scattering in phantom, especially for wide beam widths.